A strong spatial association between e‐waste burn sites and childhood lymphoma in the West Bank, Palestine. Issue 3 (22nd October 2018) - Davis, John‐Michael; Garb, Yaakov
Abstract : A paper in the International Journal of Cancer analyzed Palestinian cancer registry data in the West Bank from 1998 to 2007, showing a cluster of elevated cancer incidence in rural villages in south‐west Hebron, with a 4.10 risk ratio for childhood lymphoma ( p = 0.0023). The paper called for investigation of the environmental or genetic etiologies of this cluster in an otherwise unremarkable rural area. 1 Our research in these same villages shows them to be the center of an extensive informal electronic and electrical waste (e‐waste) dismantling industry in Palestine, operating for almost two decades. This entails extensive open‐burning of e‐waste components to extract valuable metals or dispose of nonvaluable waste, releasing high concentrations of hazardous contaminants, which may be an important factor in the elevated cancer incidence. We offer a first step in assessing this link. We applied a novel multitemporal object‐based method to map the prevalence and intensity of e‐waste burn sites in the entire Hebron Governorate (1, 060 km 2 ) between 1999 and 2007. A weighted standard deviation ellipse of cumulative burn activity covers a smaller area (247 km 2 ) very closely matching the childhood lymphoma cluster: it contains 85% of the core cluster area (RR of 4.1), and falls almost entirely (95%) within the broader area of elevated risk (RR of 2.8). Extensive international evidence linking informal e‐waste processing to elevated cancer incidence and this strong spatial association of e‐waste burning activity with a distinct unexplained cancer cluster in the Palestinian context signals the urgent need for investigation and intervention. Abstract : What's new? Researchers have combined field study and remote sensing analysis to identify the likely cause of an unexplained childhood cancer cluster in a rural region of the West Bank. They developed a multitemporal mapping strategy of e‐waste burn sites, demonstrating a strong spatial association between a concentrated area of e‐waste burn sites and the cancer cluster. In light of this association, they recommend stopping, assessing, and remediating environmentally harmful e‐waste burning practices and hope for future success of their method in mapping e‐waste burning activities worldwide.